Change of Management Control from the Balanced Scorecard to Budgeting: Case-Study Evidence from a Commercial Bank - Kapiyangoda, K.; Gooneratne, T.N. (My University, 2013)
Althoughthe balanced scorecard (BSC) is claimed to be conceptually superior to budgeting,not all BSC implementations get sustained, and some organizations even move back to budgetary control systems.Using the qualitative case study approach,this study investigates the reasons for the change of management controlfrom BSC to budgeting in a Sri Lankan commercial bank.To capture thesereasons, a revised Accounting Change Model of Cobb, Helliar, and Inns (1995) was used. This study contributes to literature by further developing Cobb et al.’s (1995) Model, by sub-categorizing the momentum for change into three elements: people, processes and external triggers, based on the case study evidence.
Keywords: Management control systems; Budgetary control; Balanced scorecard; Bank; Sri Lanka